Correlation Between Duration of Work and Candida Colony Counts and Trichomonas vaginalis Infection among Commercial Sex Workers - Intan Dwi Nurhidayah; Nia Riyana Nurcahyani; Dwi Haryatmi (Jurnal Biologi Tropis, 2026)
Sexually transmitted infections remain a major health problem among high-risk groups, including female commercial sex workers, in whom Candida spp. and Trichomonas vaginalis are frequently identified as causative agent. This study aimed to determine the relationship between duration of work and Candida colony counts as well as Trichomonas vaginalis infection among commercial sex workers. An analytical observational study with a cross-sectional design was conducted involving 30 respondents. Detection of Trichomonas vaginalis was performed microscopically using wet mount and dry smear preparations, while Candida colony counts were determined through urine culture on CHROM Agar Candida media and confirmed by Lactophenol Cotton Blue (LPCB) staining. Data were analyzed using the Chi-Square and Fisher’s Exact tests. The results showed that 56,7% of respondents had worked for more than three years, 56,7% had Candida colony counts greater that 251 with dominant species Candida krusei and Candida parapsilosis, and 33.3% tested positive for Trichomonas vaginalis. Statistical analysis demonstated a significant association between duration of work and Candida colony counts (p=0.000) as well as Trichomonas vaginalis infection (p=0.001). In conclusion, a longer duration of employment as a commercial sex worker is associated with an increased risk of Candida colonization and Trichomonas vaginalis infection.